Advanced Control for Grid-Connected System With Coordinated Photovoltaic and Energy Storage - Zhu, Yujie; Chen, Guanhua (Frontiers in Energy Research, 2022)
The large-scale new energy sources such as photovoltaic power generation reduces the original damping and inertia of the power system, resulting in the oscillation of the system. Self-adaptive virtual synchronous generator (SDVSG) controlled grid-connected inverters can provide virtual damping and inertia to support the frequency and voltage of the grid. Combining SDVSG control with stand-alone PV systems, a mainstream solution is to configure energy storage systems for them. In this paper, a grid-connected PV storage system with SDVSG is proposed with coordination control; an adaptive variable-step conductivity increment method is adopted to achieve the maximum power point tracking (MPPT) for PV array, and variable domain fuzzy logic control methods of DC-DC converter are implemented as well. Finally, the simulation results prove the system has strong robustness and could handle the perturbations.